Radiação ultravioleta-C (UV-C) em sementes de algodoeiro - Fernandes, Gabriel Aragão (2024)
Cotton production is affected by salinity, drought, high air temperatures, etc., which increases the production of Reactive Oxygen Species (ROS). High levels of ROS cause cellular damage, in this sense, new technologies such as seed conditioning have been tested with the aim of previously activating the plant defense system, providing greater robustness to plants. Therefore, this study aimed to evaluate the physiological responses of cotton plants subjected to different levels of ultraviolet radiation. This study was divided into two stages: I – A joint analysis was carried out with data obtained through two experiments using the BRS 286 genotype, sensitive to water deficit, under the following levels of UV-C 0.00; 2.87; 4.78; 5.74 and 11.48 kJ m-2, using a randomized block design (DBC), with four replications. Germination percentage, percentage of normal and abnormal seedlings, cotyledon and seedling dry matter, shoot and root length and vigor were evaluated, based on the tetrazolium test. The regression test was performed for significant variables, and the Pearson correlation test was performed for all variables. II – The experiment was carried out in a factorial scheme in DBC, in which the BRS 286 and DP 555 BGRR genotypes were evaluated at the following levels 0.00; 5.74; 11.48 and 17.22 kJ m-2, with four repetitions. The same evaluations as in stage I were carried out, in addition, biochemical responses were evaluated. The Tukey test was performed to compare genotypes, regression to compare UV-C levels and genetic parameters were calculated. The BRS 286 genotype showed a reduction in the number of normal seedlings and in vigor, according to exposure to UV-C, while the DP 555 BGRR genotype did not change its vigor parameters. The damages correlated to UV-C were hypocotyl death and root deformation. During the tetrazolium test it was possible to observe the death of the embryonic axis and damage to the root cylinder according to the increase in the UV-C level. Corroborating the results of the germination and tetrazolium tests, biochemical analyzes demonstrated that the oxidative damage parameters of the BRS 286 genotype were superior when compared to DP 555 BGRR. The behavior of the cotton plant regarding exposure to UV-C proved to be variable according to the genotype, showing differentiation in terms of tolerance to water deficit, where the tolerant genotype did not show loss of vigor.